Reliability of Uncertainty Tolerance Scales Implemented Among Physicians and Medical Students: A Systematic Review and Meta-Analysis. (1st March 2022) - Stephens, Georgina C.; Karim, M. Nazmul; Sarkar, Mahbub; Wilson, Adam B.; Lazarus, Michelle D.
Abstract : Purpose: Uncertainty tolerance (UT) is a construct describing individuals' perceptions of, and responses to, uncertainty across their cognition, emotion, and behavior. Various UT scales have been designed for physician and medical student populations. However, links between UT and other variables (e.g., training stages) are inconsistent, raising concerns about scale reliability and validity. As reliability is a precondition for validity, a necessary first step in assessing UT scales' efficacy is evaluating their reliability. Accordingly, the authors conducted a meta-analysis of the reliability of UT scales designed for, and implemented among, physician and medical student populations. Method: In 2020, the authors searched 4 electronic databases alongside a citation search of previously identified UT scales. They included English-language, peer-reviewed studies that implemented UT scales in physician and/or medical student populations and reported reliability evidence. A meta-analysis of studies' Cronbach's alphas evaluated aggregated internal consistency across studies; subgroup analyses evaluated UT scales by named scale, population, and item characteristics. Results: Among 4, 124 records screened, 35 studies met the inclusion criteria, reporting 75 Cronbach's alphas. Four UT scales appeared in at least 3 included studies: Physicians' Reactions to Uncertainty scale 1990 (PRU1990) and 1995 (PRU1995) versions, Tolerance for Ambiguity scale (TFA), and Tolerance of Ambiguity in Medical Students and Doctors scale (TAMSAD). The scores from these scales ranged in reliability from very good (PRU1990: 0.832, PRU1995: 0.818) to respectable (TFA: 0.761, TAMSAD: 0.711). Aggregated internal consistency was significantly higher ( P < .001) among physicians (0.797) than medical students (0.711). Conclusions: UT scales generally demonstrated respectable internal consistency when administered among physicians and medical students, yet the reliability among medical students was significantly lower. The authors caution against using UT scores for decision-making purposes (e.g., applicant selection, program evaluation), especially among medical student populations. Future research should explore the reasons underlying these observed population differences.